Repliche a una pretesa critica di Schatzman a Freud sul caso clinico del presidente Schreber. Contributi eziologici precipui della psicanalisi sulla paranoia (Parte prima) - Tosto, Maria Grazia (Metapsychologica - rivista di psicanalisi freudiana, 2022)
This article, as pars destruens, constitutes the first of two parts of a study aimed towards a rereading of Freud’s Psycho-analytic notes (Psychoanalytische Bemerkungen, 1910) on the clinical case of President Schreber, described in the latter’s auto-biographical book entitled Memoirs of my nervous illness (Denkwürdigkeiten eines Nervenkranken, 1903). Taking a cue from Morton Schatzman’s essay entitled Soul Murder: Persecution in the Family (1973) – which devotes ample space to the examination of the psycho-pathogenic potential of certain family contexts and the educational methods that are practiced therein while recognizing the undoubted value of the contribution of the American psychiatrist. In particular the attention he pays both to the absurd «educational» precepts contained in the writings of Schreber’s father, and for the surprising similarities and correspondences existing between many of those precepts and the delusional ideas from which his son later suffered. It nevertheless aims to reply to Schatzman and, more specifically, to the criticism that the latter moves towards Freud, who, in his opinion would not have recognized the causal role of paternal persecutory behavior in the genesis of the son’s paranoid imagery. Seeing in Schatzman’s speech an ambiguity in the use of the concept of cause itself, this article also focuses on some other weak points which include firstly, the absence of an etiological reference framework suitable to support the alleged causal explanations and secondly, an incomplete consideration of the pathogenic effect of the repression of a possible homosexual disposition in the child. (An explanation of the strengths of Freud’s analysis on the other hand will be the subject of the second part, which has the function of pars construens).